International guidelines on stage III N2 nonsmall cell lung cancer: surgery or radiotherapy?. Issue 1 (17th February 2020) - Putora, Paul Martin; Leskow, Pawel; McDonald, Fiona; Batchelor, Tim; Evison, Matthiew
Stage III N2 nonsmall cell lung cancer (NSCLC) is a complex disease with poor treatment outcomes. For patients in whom the disease is considered technically resectable, the main treatment options include surgery (with neoadjuvant or adjuvant chemotherapy/neoadjuvant chemoradiotherapy (CRT)) or CRT followed by adjuvant immunotherapy (dependent on programmed death ligand 1 status). As there is no clear evidence demonstrating a survival benefit between these options, patient preference plays an important role. A lack of a consensus definition of resectability of N2 disease adds to the complexity of the decision-making process. We compared 10 international guidelines on the treatment of NSCLC to investigate the recommendations on preoperatively diagnosed stage III N2 NSCLC. This comparison simplified the treatment paths to multimodal therapy based on surgery or radiotherapy (RT). We analysed factors relevant to decision-making within these guidelines. Overall, for nonbulky mediastinal lymph node involvement there was no clear preference between surgery and CRT. With increasing extent of mediastinal nodal disease, a tendency towards multimodal treatment based on RT was identified. In multiple scenarios, surgery or RT-based treatments are feasible and patient involvement in decision-making is critical. For many patients with stage III N2 NSCLC, radiotherapy or surgery are options and should be discussed with the patient http://bit.ly/2Z39MW5